1991
DOI: 10.1139/l91-053
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of recycled asphalt pavements at low temperatures

Abstract: This paper summarizes the results of a study conducted to evaluate the behaviour of recycled asphalt pavements with respect to low-temperature cracking. For this purpose, a recycled mix consisting of 45.2% reclaimed materials and 54.8% virgin materials as well as a virgin control mix were used in the research program. In the design of both mixes, their initial properties were kept as close as possible to each other to allow for a proper comparison between recycled and virgin asphalt pavements. Using mix proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…For example, Tam et al (8) found that mixes with RAP are less resistant to thermal cracking than non-recycled mixtures, while Kandhal et al (9) found no significant difference in cracking performance, and Sargious and Mushule (10) found that a recycled mixture performed better than a virgin mixture in terms of cracking. The mixture behavior is responsive to binder properties at low, intermediate and high temperatures.…”
Section: Summary Of Literature Reviewmentioning
confidence: 99%
“…For example, Tam et al (8) found that mixes with RAP are less resistant to thermal cracking than non-recycled mixtures, while Kandhal et al (9) found no significant difference in cracking performance, and Sargious and Mushule (10) found that a recycled mixture performed better than a virgin mixture in terms of cracking. The mixture behavior is responsive to binder properties at low, intermediate and high temperatures.…”
Section: Summary Of Literature Reviewmentioning
confidence: 99%
“…Through literature analysis, transfer law of aged asphalt from old aggregate to new aggregate accords with convective mass transfer theory [6]. Further analysis of convective mass transfer theory is helpful to understand the mechanism of asphalt transfer and recycling.…”
Section: Analysis For Transfer Mechanism Of Asphalt Binder Based mentioning
confidence: 60%
“…Similar to conventional non-modified asphalt binder, polymer modified binder also becomes harden due to the weathering [5,6] . To confirm the aging performance of polymer modified asphalt binder, the force-ductility tests were conducted for non-modified binder and styrene-butadiene-styrene block copolymers (SBS) modified asphalt binder.…”
Section: Introductionmentioning
confidence: 99%